Additive fabrication of nanostructures with focused soft X-rays - Späth, Andreas; TU, Fan; Vollnhals, Florian; Drost, Martin; Krick Calderon, Sandra; Watts, Benjamin; Fink, Rainer; Marbach, Hubertus (RSC Advances, 2016)
We report on a novel technique for the fabrication of metallic nanostructures via soft X-ray irradiation of precursor molecules supplied from the gas phase. With this technique we were able to produce localized Co nanostructures with a growth rate and purity competitive with electron beam induced deposition. We demonstrate that our approach exhibits significant selectivity with respect to incident photon energy leading to enhanced growth for resonant absorption energy of the precursor molecule. Based on this finding we propose a unique new pathway of selective deposition from precursor mixtures. Furthermore, we investigated the growth rate with respect to precursor pressure and growth time and discuss the potential resolution limits of this new technique.
EAM Import::2019-03-13

Carbon Dioxide Capture by an Amine Functionalized Ionic Liquid: Fundamental Differences of Surface and Bulk Behavior - Niedermaier, Inga; Bahlmann, Matthias; Papp, Christian; Kolbeck, Claudia; Wei, Wei; Krick Calderon, Sandra; Grabau, Mathias; Schulz, Peter; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of the American Chemical Society, 2014)
Carbon dioxide (CO2) absorption by the amine-functionalized ionic liquid (IL) dihydroxyethyl dimethylammonium taurinate at 310 K was studied using surface- and bulk-sensitive experimental techniques. From near-ambient pressure X-ray photoelectron spectroscopy at 0.9 mbar CO2, the amount of captured CO2 per mole of IL in the near-surface region is quantified to similar to 0.58 mol, with similar to 0.15 mol in form of carbamate dianions and similar to 0.43 mol in form of carbamic acid. From isothermal uptake experiments combined with infrared spectroscopy, CO2 is found to be bound in the bulk as carbamate (with nominally 0.5 mol of CO2 bound per 1 mol of IL) up to similar to 2.5 bar CO2, and as carbamic acid (with nominally 1 mol CO2 bound per 1 mol IL) at higher pressures. We attribute the fact that at low pressures carbamic acid is the dominating species in the near-surface region, while only carbamate is formed in the bulk, to differences in solvation in the outermost IL layers as compared to the bulk situation.

CO oxidation on Pt(111) at near ambient pressures - Krick Calderon, Sandra; Grabau, Mathias; Ovari, L.; Kress, B.; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2016)
The oxidation of CO on Pt(111) was investigated simultaneously by near ambient pressure X-ray photoelectron spectroscopy and online gas analysis. Different CO:O reaction mixtures at total pressures of up to 1 mbar were used in continuous flow mode to obtain an understanding of the surface chemistry. By temperature-programmed and by isothermal measurements, the onset temperature of the reaction was determined for the different reactant mixtures. Highest turnover frequencies were found for the stoichiometric mixture. At elevated temperatures, the reaction becomes diffusion-limited in both temperature-programmed and isothermal measurements. In the highly active regime, no adsorbates were detected on the surface; it is therefore concluded that the catalyst surface is in a metallic state, within the detection limits of the experiment, under the applied conditions. Minor bulk impurities such as silicon were observed to influence the reaction up to total inhibition by formation of non-platinum oxides.

Exploring the fabrication of Co and Mn nanostructures with focused soft x-ray beam induced deposition - TU, Fan; Späth, Andreas; Drost, Martin; Vollnhals, Florian; Krick Calderon, Sandra; Fink, Rainer; Marbach, Hubertus (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2017)
Focused soft X-ray beam induced deposition of metallic deposits from metal organic precursors is a promising novel technique for additive nanostructure fabrication. In the present work, the authors present a comparative study for deposition and in situ characterization of Co and Mn nanostructures in a scanning transmission x-ray microscope. The authors detect a significant selectivity of the deposition process with respect to the incident photon energy that arises from the enhanced x-ray absorption cross section of the precursor molecules for near-threshold excitation. This effect has been investigated for the L2,3-edges of the respective metal centers of two different precursor molecules as well as the N and O K-edges of the respective ligands. The authors find a photon-limited growth mode for deposition from cobalt tricarbonyl nitrosyl [Co(CO)3NO], while the process is precursor-limited for methylcyclopentadienyl manganese tricarbonyl [MeCpMn(CO)3] possibly due to a comparably low vapor pressure of the latter precursor.
EAM Import::2019-03-14

Growth of Stable Surface Oxides on Pt(111) at Near-Ambient Pressures - Fantauzzi, Donato; Krick Calderon, Sandra; Mueller, Jonathan E.; Grabau, Mathias; Papp, Christian; Steinrück, Hans-Peter; Senftle, Thomas P.; van Duin, Adri C. T.; Jacob, Timo (Angewandte Chemie-International Edition, 2017)
Detailed knowledge of the structure and degree of oxidation of platinum surfaces under operando conditions is essential for understanding catalytic performance. However, experimental investigations of platinum surface oxides have been hampered by technical limitations, preventing in situ investigations at relevant pressures. As a result, the time-dependent evolution of oxide formation has only received superficial treatment. In addition, the amorphous structures of many surface oxides have hindered realistic theoretical studies. Using near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) we show that a time scale of hours (t≥4 h) is required for the formation of platinum surface oxides. These experimental observations are consistent with ReaxFF grand canonical Monte Carlo (ReaxFF-GCMC) calculations, predicting the structures and coverages of stable, amorphous surface oxides at temperatures between 430–680 K and an O partial pressure of 1 mbar.
Keywords: interfaces; kinetics; oxidation; phase transitions; surface chemistry

Interfaces of ionic liquids and transition metal surfaces - Adsorption, growth, and thermal reactions of ultrathin [C 1C 1Im] [Tf 2N] films on metallic and oxidised Ni(111) surfaces - Cremer, Till; Wibmer, Leonie; Krick Calderon, Sandra; Deyko, Alexey; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2012)
Ultrathin films of the ionic liquid 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([C C Im][Tf N]) were deposited on differently terminated Ni(111) single crystal surfaces. The initial wetting behaviour, the growth characteristics, the molecular arrangement at the interface, and thermal reactivity were investigated using angle-resolved X-ray photoelectron spectroscopy (ARXPS). On clean Ni(111), the initial growth occurs in a layer-by-layer mode. At submonolayer coverages up to at least 0.40 ML, a preferential arrangement of the IL ions in a bilayer structure, with the imidazolium cations in contact with the Ni surface atoms and the anions on top of the cation, is deduced. For higher coverages, a transition to a checkerboard-type arrangement occurs, which is most likely due to repulsive dipole-dipole interactions in the first layer. An overall preference for a checkerboard-type adsorption behaviour, i.e., anions and cations adsorbing next to each other, is found on the oxygen-precovered O(√3×√3)R30°Ni(111) surface. The thermal stability of adsorbed IL layers on Ni(111) and on a fully oxidised Ni(111) surface was studied by heating the layers to elevated temperatures. For clean Ni(111) reversible adsorption takes place. For the oxidised surface, however, only cation-related moieties desorb, starting at ∼450 K, while anion-related signals remain on the surface up to much higher temperatures. © 2012 the Owner Societies.

Near ambient pressure XPS investigation of the interaction of ethanol with Co/CeO2(1 1 1) - Ovari, L.; Krick Calderon, Sandra; Lykhach, Yaroslava; Libuda, Jörg; Erdohelyi, A.; Papp, Christian; Kiss, J.; Steinrück, Hans-Peter (Journal of Catalysis, 2013)
Near ambient pressure X-ray photoelectron spectroscopy was applied to study the interaction of ethanol (CHCHOH) with a well-ordered CeO(1 1 1) film on Cu(1 1 1) and with a Co/CeO(1 1 1)/Cu(1 1 1) model catalyst. The oxidation state of the surface and the chemical nature of reaction intermediates were analyzed. At 300 K, the oxidation state of ceria decreased gradually with increasing ethanol pressure. At a constant pressure of 0.1 mbar, the reduction of Ce to Ce increased significantly between 320 and 600 K due to a higher mobility of oxygen or Ce centers at elevated temperatures. The main intermediate, ethoxide, was formed by dissociative adsorption of ethanol at room temperature. No coke formation was observed up to 600 K on CeO. Upon deposition of metallic cobalt, partial reduction of ceria was observed, leading to the formation of Co sites but still leaving metallic Co in the metal particles. During the reaction of ethanol with the Co/CeO(1 1 1) model catalyst, the amount of Co decreased drastically with increasing temperature, and at 600 K, the majority of Co was metallic. This process was accompanied by the severe reduction of ceria and the formation of significant carbon deposits. © 2013 Elsevier Inc. All rights reserved.

Reactivity of TiO2 Nanotube-Supported Platinum Particles in the CO Oxidation Reaction - Krick Calderon, Sandra; Grabau, Mathias; Yoo, Jeong Eun; Killian, Manuela; Schmuki, Patrik; Steinrück, Hans-Peter; Papp, Christian (ChemCatChem, 2017)
The CO oxidation on different platinum model catalysts, in particular differently sized Pt particles on vertically aligned TiO nanotubes (d=80, l=200nm) was investigated by near-ambient-pressure X-ray photoelectron spectroscopy and simultaneous online gas analysis. The results are compared to the behavior on a TiO(110) rutile crystal with a similar Pt coverage and a Pt(111) single crystal. Temperature-programmed reaction experiments at total pressures of 10 to 1.0mbar, and a CO/O ratio of 1:4 were performed to evaluate the reactivity of the samples. The onset temperature of the reaction on the Pt/TiO nanotube samples was found to be lower than on Pt(111) and Pt/TiO(110) and to decrease with decreasing particle size. For all particle samples, a steep increase in reaction rate at a defined temperature was observed, and at high temperatures the reaction became mass transfer-limited in all cases. Isothermal measurements showed that no CO is adsorbed on the particles when CO oxidation has a high activity and metallic platinum is the active catalyst. Ageing of the TiO-supported samples is observed resulting in changes of the reaction onset and CO conversion.
Keywords: Nanotubes; Oxidation; Platinum; Supported catalysts; X-ray absorption spectroscopy

Spectroscopic Observation and Molecular Dynamics Simulation of Ga Surface Segregation in Liquid Pd-Ga Alloys - Grabau, Mathias; Erhard, Jannis; Taccardi, Nicola; Krick Calderon, Sandra; Wasserscheid, Peter; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2017)
Liquid binary Pd-Ga alloys with low Pd contents of 0.8, 1.8, and 4.7at% of Pd were examined as a function of sample temperature in ultra-high vacuum by using angle-resolved XPS. Upon cooling from 750 to 400K, a pronounced temperature-dependence of the Pd concentration in the liquid phase was observed, which was explained by the transition from the pure liquid phase to a two-phase system, consisting of a solid Ga5Pd phase and a Pd-depleted liquid Pd-Ga alloy. In the liquid Pd-Ga alloy, Pd is always depleted from the topmost interface layer, as deduced from angle-resolved XPS at 0 and 80 degrees emission, independent of temperature and Pd concentration. This observation is interpreted as an inhomogeneous depth distribution function of Pd, that is, the segregation of Ga to the surface of the liquid phase. The results of a DFT-based molecular dynamics simulation (MD) independently show interfacial stratification of Ga and an inhomogeneous Pd distribution along the surface normal. The evaluation of the experimental data with a rigid layer model based on the MD calculations leads to excellent agreement with the simulation.
Keywords: DFT MD; gallium; liquid-metal catalysis; palladium; XPS

Surface enrichment of Pt in Ga2O3 films grown on liquid Pt/Ga alloys - Grabau, Mathias; Krick Calderon, Sandra; Rietzler, Florian; Niedermaier, Inga; Taccardi, Nicola; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2016)
The formation of surface GaO films on liquid samples of Ga, and Pt-Ga alloys with 0.7 and 1.8 at.% Pt was examined using near-ambient pressure (NAP) X-ray photoelectron spectroscopy (XPS). Thickness, composition and growth of the oxide films were deduced as a function of temperature and Pt content of the alloys, in ultra-high vacuum and at oxygen pressures of 3 × 10, 3 × 10 and 1 mbar. We examined oxide layers up to a thickness of 37 Å. Different growth modes were found for oxidation at low and high pressures. The formed GaO oxide films showed an increased Pt content, while the pristine GaPt alloy showed a surface depletion of Pt at the examined temperatures. Upon growth of GaO on Pt/Ga alloys a linear increase of Pt content was observed, due to the incorporation of 3.6 at.% Pt in the GaO. The Pt content in GaO, at the examined temperatures and bulk Pt concentrations is found to be independent of pressure, temperature and the nominal Pt content of the metallic alloy.
Keywords: Bimetallic catalysts; Gallium oxide; NAP XPS; Pt/Ga alloys

Synthesis, characterization, and photoinduced energy and electron transfer in a supramolecular tetrakis (ruthenium(II) phthalocyanine) perylenediimide pentad - Jimenez, Angel J.; Grimm, Bruno; Gunderson, Victoria L.; Vagnini, Michael T.; Krick Calderon, Sandra; Salome Rodriguez-Morgade, M.; Wasielewski, Michael R.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2011)
Metal coordination was probed as a versatile approach for designing a novel electron donor/acceptor hybrid [PDIpy Ru(CO)Pc ] (1), in which four pyridines placed at the bay region of a perylenediimides (PDIpy ) coordinate with four ruthenium phthalocyanine units [Ru(CO)Pc]. This structural motif was expected to promote strong electronic coupling between the electron donors and the electron acceptor, a hypothesis that was confirmed in a full-fledged physicochemical investigation focusing on the ground and excited state reactivities. As far as the ground state is concerned, absorption and electrochemical assays indeed reveal a notable redistribution of electron density, that is, from the electron-donating [Ru(CO)Pc] to the electron-accepting PDIpy . The most important thing to note in this context is that both the [Ru(CO)Pc] oxidation and the PDIpy reduction are rendered more difficult in 1 than in the individual building blocks. Likewise, in the excited state, strong electronic communication is the inception for a rapid charge-transfer process in photoexcited 1. Regardless of exciting [Ru(CO)Pc] or PDIpy , spectral characteristics of the [RuPc] radical cation (broad absorptive features from 425 to 600 nm with a maximum at 575 nm, as well as a band centered at 725 nm) and of the PDI radical anion (780 nm maximum) emerge. The correspondingly formed radical ion pair state lasts for up to several hundred picoseconds in toluene, for example. On the other hand, employing more polar solvents, such as dichloromethane, destabilizes the radical ion pair state. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.